The late endosome-resident lipid bis(monoacylglycero)phosphate is a cofactor for Lassa virus fusion. - Ruben M Markosyan (Public Library of Science (PLoS), 2021)
Arenavirus entry into host cells occurs through a low pH-dependent fusion with late endosomes that is mediated by the viral glycoprotein complex (GPC). The mechanisms of GPC-mediated membrane fusion and of virus targeting to late endosomes are not well understood. To gain insights into arenavirus fusion, we examined cell-cell fusion induced by the Old World Lassa virus (LASV) GPC complex. LASV GPC-mediated cell fusion is more efficient and occurs at higher pH with target cells expressing human LAMP1 compared to cells lacking this cognate receptor. However, human LAMP1 is not absolutely required for cell-cell fusion or LASV entry. We found that GPC-induced fusion progresses through the same lipid intermediates as fusion mediated by other viral glycoproteins-a lipid curvature-sensitive intermediate upstream of hemifusion and a hemifusion intermediate downstream of acid-dependent steps that can be arrested in the cold. Importantly, GPC-mediated fusion and LASV pseudovirus entry are specifically augmented by an anionic lipid, bis(monoacylglycero)phosphate (BMP), which is highly enriched in late endosomes. This lipid also specifically promotes cell fusion mediated by Junin virus GPC, an unrelated New World arenavirus. We show that BMP promotes late steps of LASV fusion downstream of hemifusion-the formation and enlargement of fusion pores. The BMP-dependence of post-hemifusion stages of arenavirus fusion suggests that these viruses evolved to use this lipid as a cofactor to selectively fuse with late endosomes.